Intentional saccadic eye movements in patients with vestibular migraine - Pan Gu; Jing Feng; Lipeng Cai; Huimin Fan; Hailing Wang; Xiaokun Geng; Yuchuan Ding (Environmental Disease)
Objectives: Patients with vestibular migraine (VM) show a significant decrease in gray matter cortical regions associated with pain and vestibular processing, as revealed by head functional magnetic resonance imaging. We predict that these changes can be reflected in intentional saccadic eye movements. This study aims to establish whether there are abnormalities in intentional saccadic eye movements in patients with VM. Subjects and Methods: This is a retrospective study involving two groups of patients, including 39 patients in the VM group and 38 patients in the control group. The VM group and control group matched for age and gender were collected from Beijing Luhe Hospital affiliated with Capital Medical University, between June 2021 and May 2022. All patients received antisaccade (AS) and memory-guided saccade (MGS) tasks. Results: Compared with the control group, there were no significant differences in VM group in latency and gain of ASs. However, there were significant differences in the AS error rate between the two groups (right side 44% in VM and 32% in the control group; P = 0.041, left side 41% in VM and 29% in the control group; P = 0.011), with higher error rates observed in the VM group compared to the control group. Compared with the control group, there were no significant differences in the accuracy and final eye position gain of MGSs. However, there were significant differences in the valid saccade accurate percentage of MGS between the two groups (right side 59% in VM and 81% in the control group; P = 0.009, left side 59% in VM and 90% in the control group; P = 0.012), with lower accurate percentages observed in patients with VM compared to the normal control group. Furthermore, the latency of MGS between the two groups differed significantly (right side 677 ms in VM and 491.5 ms in the control group; P = 0.024, left side 670 ms in VM and 555 ms in the control group; P = 0.024), with longer latencies observed in patients with VM compared to normal control group. The results showed that VM disease duration had a positive correlation with the AS error rate (right: P =0.043, r = 0.326; left: P =0.000, r = 0.535). Conclusions: We found abnormalities in the AS and MGS tasks in patients with VM. The duration of VM is positively correlated with the AS error rate. Our study discovered that in addition to headache, dizziness, and autonomic symptoms, VM patients also exhibit impaired intentional saccadic eye movements, which may be related to reduced gray matter volume involved in pain and vestibular processing and cognitive impairment in VM patients.